TO RESERVE THE PRIORITY FOR HOME-SELECTED CABBAGE VARIATIES IS A TASK OF THE STATE-LEVEL IMPORTANCE - V.I. Startsev; L.L. Bondareva (Овощи России, 2011)
The challenges concerning the development of cabbage seed management and production in Russia are to be resolved by combined approaches in order to fully supply the vegetable market and population with home-selected varieties and heterosis hybrids.